Parasites & Vectors - Kostadinova, Aneta
Parasites & Vectors is an open access, peer-reviewed online journal dealing with the biology of parasites, parasitic diseases, intermediate hosts, vectors and vector-borne pathogens. Manuscripts published in this journal will be available to all worldwide, with no barriers to access, immediately following acceptance. However, authors retain the copyright of their material and may use it, or distribute it, as they wish. In addition to the traditional and well-established areas of science in these fields, we also aim to provide a vehicle for publication of the rapidly developing resources and technology in parasite, intermediate host and vector genomics and their impacts on biological research. We are able to publish movies and also large datasets and extensive results, frequently associated with genomic and post-genomic technologies, which are not readily accommodated in traditional journals. Manuscripts addressing broader issues, for example economics, social sciences and global climate change in relation to parasites, vectors and disease control, are also welcomed. Manuscripts on all aspects of the basic and applied biology of parasites, intermediate hosts, vectors and vector-borne pathogens will be considered. In addition to the traditional and well-established areas of science in these fields, we also aim to provide a vehicle for publication of the rapidly developing resources and technology in parasite, intermediate host and vector genomics and their impacts on biological research. We are able to publish large datasets and extensive results, frequently associated with genomic and post-genomic technologies, which are not readily accommodated in traditional journals. Manuscripts addressing broader issues, for example economics, social sciences and global climate change in relation to parasites, vectors and disease control, are also welcomed. The electronic format of the journal offers interesting opportunities for authors. For example, in addition to the publication of large datasets, derived from field and laboratory studies, there is no limit to the number of color illustrations that can be included. Animations, slide shows and movie clips are acceptable, as also are links to relevant material on other websites. No additional charge will be made for these.